An Adaptive, Intelligent Control System for Slag Foaming - Wilson, Eric L.; Karr, Charles L.; Bennett, James P. (Applied intelligence (Dordrecht, Netherlands), 2004)
Slag foaming is a steel-making process that has been shown to improve the efficiency of electric arc furnace plants. Unfortunately, slag foaming is a highly dynamic process that is difficult to control. This paper describes the development of an adaptive, intelligent control system for effectively manipulating the slag foaming process. The level-2 intelligent control system developed is based on three techniques from the field of computational intelligence (CI): (1) fuzzy logic, (2) genetic algorithms, and (3) neural networks. Results indicate that the computer software architecture presented in this paper is suitable for effectively manipulating complex engineering systems characterized by relatively slow process dynamics like those of a slag foaming operation.